Activation energy of metal dissolution in local pit environments. (December 2021) - Li, Tianshu; Wu, Jun; Guo, Xiaolei; Panindre, Anup M.; Frankel, Gerald S.
Abstract: Metal dissolution kinetics of stainless steels 316L, 304, 430, and pure Fe in local pit environments were studied at temperatures from 20 to 50 °C. A method was introduced to calculate the activation energy of pit dissolution ( Δ G a * ) at a fixed pit environment and a given potential. Δ G a * of the alloys is in the order: SS316L > SS304 > SS430 > Pure Fe, which follows the same order as their pitting potentials. The cathodic reaction at the pit bottom surface influences the pit dissolution behavior and this effect increases with increasing pit depth and temperature. Additionally, a perspective on the prediction of critical pitting temperature using Δ G a * is proposed. Highlights: Metal dissolution kinetics in local pit environments were studied at different temperatures. A method was introduced to calculate activation energy ( Δ G a * ) of pit dissolution. The order of Δ G a * for different alloys follows the same order as their pitting potentials. Rate of cathodic reaction at the pit surface increases with increasing pit depth and temperature. Perspective on the prediction of critical pitting temperature using Δ G a * was proposed.